Пошаговое объяснение:
Для удобства вычислений сгруппируем по парам дроби, дающие в сумме 1, а оставшиеся сложим, приведя к общему знаменателю (5*6*7=210)
1/2+1/3+1/4+1/5+1/6+1/7+2/3+2/4+2/6+2/7+3/4+3/5+3/6+3/7+4/5+4/7+5/6+6/7=
1/2+ (1/3+2/3) + (1/4+3/4) + (1/5+4/5) + (1/6+5/6) + (1/7+6/7) +2/4+ (2/6+3/6) +2/7+3/5+ (3/7+4/7) = 1/2 + 1 + 1 + 1 + 1 + 1 + 2/4+ 5/6 + 2/7+3/5 + 1 = 6 + (1/2 + 2/4) + (5/6 + 2/7+3/5) = 6 + 1 + (5*35/21 0 + 2*30/210 + 3*42/210) = 7 + (175+60+126)/210 = 7 + 361/210 = 7 + 1 151/210 = 8 151/210
Пошаговое объяснение:
( 400 :X + 5 ) - 5 = 200
400 : x + 5 = 200+5
400:x + 5 = 205
400 : x = 205 - 5
400 : x = 200
x = 400 : 200
x = 2
1000 - ( 4500 :X + 80 ) = 420
4500:x + 80 = 1000-420
4500:x + 80 = 580
4500:x = 580 - 80
4500:x = 500
x = 4500:500
x = 9
(54 :X + 30 ) x 2 = 72
54:x + 30 = 72:2
54:x + 30 = 36
54:x = 36 - 30
54:x = 6
x = 54 : 6
x = 9
8 * ( 36 + 4*X) = 480
36 + 4x = 480:8
36 + 4x = 60
4x = 60 - 36
4x = 24
x = 24 : 4
x = 6
(6*X + 12 ) : 6 = 50
6x + 12 = 50 * 6
6x + 12 = 300
6x = 300 - 12
6x = 288
x = 288 : 6
x = 48